2020
DOI: 10.3390/ijms21249686
|View full text |Cite
|
Sign up to set email alerts
|

Xenogeneic and Stem Cell-Based Therapy for Cardiovascular Diseases: Genetic Engineering of Porcine Cells and Their Applications in Heart Regeneration

Abstract: Cardiovascular diseases represent a major health concern worldwide with few therapy options for ischemic injuries due to the limited regeneration potential of affected cardiomyocytes. Innovative cell replacement approaches could facilitate efficient regenerative therapy. However, despite extensive attempts to expand primary human cells in vitro, present technological limitations and the lack of human donors have so far prevented their broad clinical use. Cell xenotransplantation might provide an ethically acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 169 publications
(168 reference statements)
0
9
0
Order By: Relevance
“…In conclusion, this study revealed that endogenous porcine PERV retroviruses are able to infect human cells in vitro, which can also occur in the case of xenotransplantation, therefore inducing negative health effects in the xenograft recipient. Observation of such cases is especially important due to the increased interest in xenogeneic and genetically modified stem cell-based therapy -the potential of porcine cells in the field of stem cell-based therapy and regenerative medicine is subject to intensive research (Galow et al, 2020). In porcine cells, PERV was characterized by high sequence variability, mainly of the pol gene, which may result in less accurate verification of its presence in the organs of donors and less effective therapy using modern PERV gene interference techniques (CRISPR, RNAi, siRNA shRNA) based on the nucleotide sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study revealed that endogenous porcine PERV retroviruses are able to infect human cells in vitro, which can also occur in the case of xenotransplantation, therefore inducing negative health effects in the xenograft recipient. Observation of such cases is especially important due to the increased interest in xenogeneic and genetically modified stem cell-based therapy -the potential of porcine cells in the field of stem cell-based therapy and regenerative medicine is subject to intensive research (Galow et al, 2020). In porcine cells, PERV was characterized by high sequence variability, mainly of the pol gene, which may result in less accurate verification of its presence in the organs of donors and less effective therapy using modern PERV gene interference techniques (CRISPR, RNAi, siRNA shRNA) based on the nucleotide sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Since pigs possess similar genetic and physiological characteristics as humans, porcine specimens including MSCs can provide valuable insights into therapeutic mechanisms and aid the development of promising therapeutic applications of MSCs to several human disorders as a xenogeneic regimen [ 7 , 8 ]. However, whether differentiated MSCs retain their immunomodulatory properties in xenogeneic application models is still not clear, despite the knowledge that internal and external stimuli affect the potential of MSCs; MSCs applied to the inflammatory sites were directly exposed with proinflammatory cytokines [ 13 , 18 , 24 ]. Therefore, we aimed to reveal changes in the immunomodulatory and migratory properties of differentiated porcine MSCs and the effects of IFN- γ licensing on differentiated MSCs in an in vitro xenogeneic application model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, safety, efficacy, and survival in the host after the application of MSCs have been validated during long-term follow-up studies in numerous clinical trials [ 1 , 4 ]. Although many studies of MSC applications have used allogeneic transplantation to reveal their therapeutic mechanism in certain diseases or defects, xenotransplanted MSCs have also presented positive and ameliorating effects in systemic lupus erythematosus, collagen-induced arthritis, and cardiovascular disease [ 1 , 7 , 13 ]. In particular, the xenogeneic application of MSCs can be adopted as an unlimited cell source when cell numbers or donors are lacking during clinical trials or when cryopreserved MSCs are not requested [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xenogeneic MSCs are ethically acceptable donor sources for cellular replacement therapy. 18 Pigs are one of the candidates for an alternative donor source of MSCs. Because of their large size, sufficient MSCs to treat one patient can be obtained from a single pig.…”
Section: Introductionmentioning
confidence: 99%
“…Xenogeneic MSCs are ethically acceptable donor sources for cellular replacement therapy 18 . Pigs are one of the candidates for an alternative donor source of MSCs.…”
Section: Introduction6mentioning
confidence: 99%